Curriculum Development Based on Constructivism Learning Theory - Gustafsson, John Ake (Jurnal Ar Ro'is Mandalika (Armada), 2021)
This research aims to determine constructivist learning theory, the advantages of constructivist learning theory, the weaknesses of constructivist learning theory and the characteristics/characteristics of constructivism. The research method used in this research is the library research method from the main source, namely journals. The curriculum is a tool designed to develop the abilities of teachers and students in solving daily problems and meeting existing needs. The discussion of this research is the understanding of constructivist learning theory which states that learning is a process in which individuals actively build their own knowledge. Constructivist learning theory has advantages and disadvantages because this theory makes students more active and creative where teachers do not only convey the knowledge they have, so there can be differences of opinion between students and teachers. One of the characteristics of constructivism is that knowledge is built based on experience or previous knowledge learning a personal interpretation of the world, an active process in which meaning is developed through experience, knowledge grows through negotiation of meaning and learning is carried out in a realistic way.